2021
DOI: 10.21037/apm-20-2121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Reduning injection in the treatment of COVID-19: a randomized, multicenter clinical study

Abstract: Background: Reduning injection is a traditional Chinese medicine (TCM) with known efficacy against a variety of viral infections, but there is no data about its efficacy against coronavirus disease 2019 (COVID-19). Methods: To explore the efficacy and safety of Reduning injection in the treatment of COVID-19, a randomized, open-labeled, multicenter, controlled trial was conducted from 12 general hospitals between 2020.02.06 and 2020.03.23. Patients with COVID-19 who met the diagnostic criteria of the "Diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
0
44
0
Order By: Relevance
“…Several herbal/traditional medicines have been investigated for the treatment of mild and severe/critical COVID-19. They come from countries with well-known traditional medicine such as China (Xia et al, 2021;Xiao et al, 2020;Xu et al, 2021;Zhou et al, 2021), India (Devpura et al, 2021;Natarajan et al, 2021;Srivastava et al, 2021), and Iran (Karimi et al, 2021;Valizadeh et al, 2020). These studies showed that herbal medicines could Antitussive treatment 0 (0.0) 4 (12.5) .050…”
Section: Discussionmentioning
confidence: 99%
“…Several herbal/traditional medicines have been investigated for the treatment of mild and severe/critical COVID-19. They come from countries with well-known traditional medicine such as China (Xia et al, 2021;Xiao et al, 2020;Xu et al, 2021;Zhou et al, 2021), India (Devpura et al, 2021;Natarajan et al, 2021;Srivastava et al, 2021), and Iran (Karimi et al, 2021;Valizadeh et al, 2020). These studies showed that herbal medicines could Antitussive treatment 0 (0.0) 4 (12.5) .050…”
Section: Discussionmentioning
confidence: 99%
“…Molecules like isorhamnetin, quercetin, luteolin, ferulic acid and others which are major components of horchata are also predominant in the Reduning injection, which was recommended in China for the treatment of pneumonia induced by COVID-19 (X. Xu et al, 2021 ). In addition, a similar list of compounds (also including acacetin ( 26 ) and kaempferol) can be found in other traditional medicines used in Chinae to treat COVID-19-induced pneumonia ( Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antipyretic mechanism of RDN might be related to the regulation of biosynthesis as well as sphingolipid metabolism of valine, leucine, and isoleucine (Gao et al, 2020). In addition, RDN was reported to possess anti-inflammatory and antiviral effects (Cao et al, 2015;Xie et al, 2020;Xu et al, 2021), which might work in treating acute tonsillitis. SHL is made from active ingredients of Forsythia suspensa (Thunb.)…”
Section: Discussionmentioning
confidence: 99%